Hubungan Antara Motivasi Belajar dan Prestasi Belajar Mahasiswa PGSD dalam Mata Kuliah Konsep Dasar IPA di Universitas Negeri Makassar - Siti Zahra Mulianti Natsir (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
Learning motivation is one of the key factors influencing students' academic achievement in higher education. This study aims to examine the relationship between learning motivation and academic achievement among students in the Basic Science Concepts course. The research subjects consisted of 161 students from the Primary School Teacher Education (PGSD) Study Program at Universitas Negeri Makassar who were enrolled in the course. A correlational quantitative method was employed, with data analyzed using the Spearman Rank test. The Kolmogorov-Smirnov normality test indicated that the data were not normally distributed (significance = 0.001), prompting the use of a non-parametric correlation test. The Spearman test results revealed a significant relationship between learning motivation and academic achievement (significance = 0.001) with a correlation coefficient of 0.325, indicating a low-strength positive correlation. These findings suggest that learning motivation contributes to students’ academic achievement, although not dominantly. Therefore, strategies to enhance learning motivation should be continuously developed to support students' academic performance, particularly in basic science learning.